Analysis Of Sansevieria Fiber Composite With Naoh Alkalization: Analisa Komposit Serat Lidah Mertua (Sansevieria) Dengan Perlakuan Alkali Naoh - Febriyanto, Eko Wahyu; Widodo, Edi (Universitas Muhammadiyah Sidoarjo, 2022)
Composites with natural fiber reinforcement have special characteristics that imitation fibers do not have. Sansevieria fiber as one of the producers of good quality natural fiber, as research has been done, has good potential to be developed. This study discusses the manufacture and characteristics of plant fiber composites (sensevieria) with a polyester matrix using the hand lay up method. This composite uses a volume fraction of 30% with woven fiber treatment and NaOH immersion as much as 0%, 4%, 7%, 10%, 13%, and 15% for 4 hours at room temperature. In this research, it is aimed to determine the mechanical properties of this composite by performing a tensile test, with the standard ASTM D638 – 03. namely: the highest tensile strength was found in the 10% NaOH immersion variable with a volume fraction of 30% matrix, amounting to 12.855 N/mm2. So that the best strain value is 0.105 in the specimen with 15% NaOH immersion and the highest elastic modulus value is found in the fiber with 4% immersion, which is 201.5 N/mm2